Oral Malignant Melanoma Initially Misdiagnosed as a Racial Pigmentation: A Case Report - Carla Patrícia Martinelli-Kläy; Marcel Leandro Laporte; Celso Ricardo Martinelli; Celso Martinelli; Tommaso Lombardi (MDPI AG, 2016)
Oral malignant melanoma (OMM) is rare, representing less than 0.5% of all oral malignancies. The most affected sites are the palate and the maxillary gingiva. Histological examination is important to establish the diagnosis of any suspicious pigmented lesion in the oral cavity, mainly if a precise clinical diagnosis is not possible. We present one case of OMM that was initially diagnosed as a racial pigmentation elsewhere 2 years earlier. Clinical examination showed multiple macules and nodules located on the hard and soft palate, gingiva and superior alveolar mucosa. These lesions were painless and presented a color variation going from dark blue to black. Histological analysis showed sheets and nests of atypical melanocytes displaying a range of shapes such as plasmacytoid, epithelioid, and round cells, located in the superficial corium extending to the deep tissues. A few tumor cells contained variable amounts of melanin. There was no invasion of blood vessels or nerve fibers. Immunohistochemical analysis revealed that the neoplastic cells were positive for HMB-45, melan-A, S-100 and negative for AE1/AE3, confirming the diagnosis of melanoma. The Ki-67 labeling index was around 25%. The patient refused any treatment and died 11 months later.